Extend Nearly Pseudo-2-Absorbing Submodules - Omar AbdulraZZaq Abdullah (Academic Science Journal)
In this paper, the concept of Extend Nearly Pseudo-2-Absorbing submodule has been presented as a generalization of 2-absorbing, nearly-2-absorbing and pseudo-2-absorbing submodules. The characterization and examples of the proposed generalization are given, as well as several properties of suggested concept are proven.